Assessment the effect of the CBT on motivation of the nursing students - Tayebeh Mehrabi; Somayeh Behzadi; Farhad Sabouri; Mousa Alavi (Wolters Kluwer Medknow Publications, 2016)
Background: Motivation to academic achievement is critical for students of medical sciences, particularly nursing students. It is directly related to high levels of achievement and quality of life. Accordingly, diminished motivation would result in academic decline, study and work desertion and exhaustion. Therefore, this study aimed to investigate the effect of cognitive behavioural intervention on the motivation for academic achievement of the nursing students. Materials and Methods: This study was conducted on 64 female nursing students who were recruited to study based on the inclusion criteria. After sampling, the subjects were randomly assigned to study and control groups. Then, cognitive behavioural intervention was administered in study group during 60 days. Academic motivation scale was filled before, after and one month after the intervention. Data were analyzed by descriptive and inferential statistical tests (Chi-square, t-test). Results: After the intervention, mean scores of academic motivation were significantly increased in study group, compared to control group (P < 0.001). Comparison of the mean scores of academic motivation in two groups revealed a significant increase in mean score of academic motivation 151.50 (20.22) after cognitive behavioural intervention (P < 0.001). Conclusions: The findings suggested that cognitive behavioural intervention was a valuable psychotherapy technique to improve academic achievement motivation among nursing students.